Post adoption evaluation model for cloud computing services utilization in universities in Kenya - Titus Mukisa, Muhambe; Orwa Ochien, Daniel (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Cloud Computing, a recent technology development presents a paradigm shift in computing, a move away from personal computers and enterprise server systems, to a cloud of computers located on the internet. Applications and resources are accessed from the cloud. The introduction of cloud computing services in Kenya by some telecommunication company like Safari Cloud from Safaricom Limited is an indicator that cloud computing technology is gaining ground and popularity locally. Technology adoption studies, which include Cloud computing adoption, have mainly been carried out in United State of America, Europe, Japan and Australia. No previous study has analyzed the acceptance and use of cloud computing services in a university setting in Kenya. In addition, no model has been advanced to explain the factors that influence acceptance and use of cloud services in the same setting. A conceptual model derived from the Unified Theory of Acceptance and Use of Technology (UTAUT) was used as a guide in this study. Survey (n=217) and Focus Group Discussion (n=12) were used as data collection instruments in an attempt to understand cloud services adoption and use. The results of partial correlation showed that Performance Expectancy and Facilitating Condition were the two main factors that significantly influence cloud services acceptance and use in the universities in Kenya. The Focus Group Discussion results established that personal ego was a factor that prevented individuals from admitting that they were socially influenced towards adoption and use of cloud services. The findings will be useful to multiple stakeholders that include; academic researchers, technology adoption and perception researchers and cloud services providers and vendors.